ANALISA KADAR NATRIUM BENZOAT PADA SAUS NASI GORENG YANG DIPAKAI PEDAGANG KAKI LIMA DI DAERAH RUNGKUT MADYA SURABAYA - Hayati, Mala (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST)
ANALISA KADAR NATRIUM BENZOAT PADA SAUS NASI GORENG YANG DIPAKAI PEDAGANG KAKI LIMA DI DAERAH RUNGKUT MADYA SURABAYAMala Hayati, S.TP, M.Kes. Prodi D3 Analis Kesehatan UM Surabaya ABSTRACTSauce is one of many favorite foods community, as a substance that can be consumed directly or as a food supost prandiallement. To extend its store sauce, sauce is often added preservatives. Used preservative sodium benzoate, where the material is constrained apost prandiallications. Sodium benzoate is used because it can inhibit the growth of bacteria at pH 2.5 to 4.0. Formulation of the problem in this study is what is the level of Sodium Benzoate in the sauce fried rice hawkers sold in the middle Rungkut Surabaya, while the purpose of the study to determine levels of Sodium Benzoate is used. This study was descriptive and spectrophotometer methods ie, with samples taken 30 sauce taken from some street vendors in Madhya Rungkut Surabaya area. Results of the study found 60% of eligible Permenkes and 40% are not eligible. This shows most of the street vendors using Permenkes qualified sauce.Key word : Natrium benzoat, Sauce